The life we almost had - Henley, Amelia (Forever, 2022)
"Anna wasn't looking for love when Adam swept her off her feet but there was no denying their connection, and she believed they would be together forever. Years later, cracks have appeared in their relationship. Anna is questioning whether their love can really be eternal when a cruel twist of fate delivers a crushing blow, and Anna and Adam are completely lost to one another. Now, Anna needs Adam more than ever, but the way back to him has life-changing consequences. Is a second chance at first love really worth the sacrifice? Anna needs to decide and time is running out.."--